Investigating the Appropriateness of Social Network Question Asking as a Resource for Blind Users - Brady, Erin; Zhong, Yu; Morris, Meredith Ringel; Bigham, Jeffrey P. (Proceedings of CSCW 2013, 2013)
Recent work has shown the potential of having remote humans answer visual questions that blind users have. On the surface social networking sites (SNSs) offer an attractive free source of human-powered answers that can be personalized to the user. In this paper, we explore the potential of blind users asking visual questions to their social networks. We present the first formal study of how blind people use social networking sites via a survey of 191 blind adults. We also explore whether blind users find SNSs an appropriate venue for Q&A through a log analysis of questions asked using VizWiz Social, an iPhone app with over 5,000 users, which lets blind users ask questions to either the crowd or friends. We then report findings of a field experiment with 23 blind VizWiz Social users, which explored question asking on VizWiz Social in the presence of monetary costs for non-social sources. We find that blind people have a large presence on social networking sites, but do not see them as an appropriate venue for asking questions due to high perceived social costs.